2021
DOI: 10.25518/1780-4507.19016
|View full text |Cite
|
Sign up to set email alerts
|

Réponse du cotonnier (Gossypium hirsutum L.) à la fertilisation minérale dans diverses zones agro-écologiques : revue quantitative

Abstract: Description du sujet. La réponse du cotonnier à la fertilisation minérale a été évaluée à travers une revue quantitative. Objectifs. Il s’agissait de (i) faire une synthèse des données disponibles sur la réponse du cotonnier à la fertilisation, (ii) modéliser le rendement en fonction des niveaux de fertilisants appliqués et (iii) identifier les facteurs environnementaux qui influencent la réponse du cotonnier à la fertilisation. Méthode. Une analyse quantitative de 71 publications scientifiques (930 traitement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The final nutrient concentration of the sequential extraction experiment (Section 3.3) showed a lower release amount of P and K when NPK is loaded in biochar compared to pure NPK fertilizer. The higher amount of nutrients released with pure NPK is due to its high solubility as supported by its total dissolution after less than 48 h (AlShamaileh et al., 2018; Amonmidé et al., 2021). In addition to lower total release amount of P and K, biochar‐based fertilizers showed a much longer release time, up to two weeks for N‐NO 3 − and K, compared to pure NPK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final nutrient concentration of the sequential extraction experiment (Section 3.3) showed a lower release amount of P and K when NPK is loaded in biochar compared to pure NPK fertilizer. The higher amount of nutrients released with pure NPK is due to its high solubility as supported by its total dissolution after less than 48 h (AlShamaileh et al., 2018; Amonmidé et al., 2021). In addition to lower total release amount of P and K, biochar‐based fertilizers showed a much longer release time, up to two weeks for N‐NO 3 − and K, compared to pure NPK.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of soil fertility reduces crop yields. In the western region of the country, where cotton ( Gossypim hirsutum L.)–maize ( Zea mays L.) rotations are predominant, current soil fertility management relies on chemical fertilizer alone, or in combination with organic amendments such as manure or compost, when available (Amonmidé et al., 2021; Yaméogo et al., 2013). Previous studies reported that mineral fertilizers are being used less because of their low accessibility, prohibitive cost, and low effects on crop yields, mainly due to soil and climatic constraints (Bationo et al., 2007; Bonzi et al., 2008; Sanogo et al., 2020).…”
Section: Introductionmentioning
confidence: 99%